Anisotropic Resistivity Surfaces Produced in ITO Films by Laser‐Induced Nanoscale Self‐organization. Issue 2 (23rd November 2020) - Lopez‐Santos, Carmen; Puerto, Daniel; Siegel, Jan; Macias‐Montero, Manuel; Florian, Camilo; Gil‐Rostra, Jorge; López‐Flores, Víctor; Borras, Ana; González‐Elipe, Agustín R.; Solis, Javier
Abstract: Highly anisotropic resistivity surfaces are produced in indium tin oxide (ITO) films by nanoscale self‐organization upon irradiation with a fs‐laser beam operating at 1030 nm. Anisotropy is caused by the formation of laser‐induced periodic surface structures (LIPSS) extended over cm‐sized regions. Two types of optimized structures are observed. At high fluence, nearly complete ablation at the valleys of the LIPSS and strong ablation at their ridges lead to an insulating structure in the direction transverse to the LIPSS and conductive in the longitudinal one. A strong diminution of In content in the remaining material is then observed, leading to a longitudinal resistivity ρL ≈ 1.0 Ω·cm. At a lower fluence, the material at the LIPSS ridges remains essentially unmodified while partial ablation is observed at the valleys. The structures show a longitudinal conductivity two times higher than the transverse one, and a resistivity similar to that of the pristine ITO film (ρ ≈ 5 × 10 −4 Ω·cm). A thorough characterization of these transparent structures is presented and discussed. The compositional changes induced as laser pulses accumulate, condition the LIPSS evolution and thus the result of the structuring process. Strategies to further improve the achieved anisotropic resistivity results are also provided. Abstract : A route for producing highly anisotropic resistivity surfaces in indium tin oxide films is presented. It is based in nanoscale self‐organization processes induced by fs‐laser processing. The approach preserves the material transparency in the visible range and its conductivity along one axis, while generating either electrical insulation or strongly increased resistance in the transverse one, depending on the processing parameters.